Models of decision-making in enterprises: Array - Rexhepi, Aziz; Petrit, Hasanaj; Rexhepi , Besarta; Meha , Arbresh (Acta Universitatis Danubius. Œconomica, 2020)
We make many decisions in a day (when we go to a restaurant, clothing store, when preparing for work, how much we need to save for a future vacation trip, etc.). It may be that our decisions are unconscious, but often we have to make conscious choices about the alternatives. Imagine a student who has finished high school. He has to decide whether to study psychology, accounting or art. How do cultural values ​​influence individual decisions? One can expect an answer to this question either from descriptive (cognitive) psychology or from cross-cultural psychology. The purpose of this study is to highlight the importance of culture in decision making, in order to reflect on the main work related to employee behaviors on motivation and the latter's influence on decision making. Descriptive theories in decision making, however, rarely consider culture factors in decision making. Therefore the study of culture and decision-making is a relatively new and unexplored field. This study discusses three examples of individual and collectivist decision-making using different methodologies to describe them. Decision-making is the choice between several options.